PROGRAM 1 AZAM AKHIRI ZAMAN KEMISKINAN RAKYAT (MISKIN TEGAR DAN MISKIN) DI KOTA SAMARAHAN - Nur Shafina, Abdullah (Universiti Malaysia Sarawak, (UNIMAS), 2019)
Program 1 AZAMis a povertyeradication program in Malaysia, was been introduced in 2010. Since its inception, the program has helped many participants increased their income. However, there are some problem in its implementation. The aim of this study is to 1) identify the effectiveness program of 1 AZAM; 2) identify the problems faced by the participants and the implementation of the 1 AZAMprogram; and 3) identify the effects of the 1 AZAMprogram on program participants. There are total of 20 participants from 1 AZAM program in Kota Samarahan. Qualitative and quantitative were used in the study. Five participants and one MPKS officer were interviewed and 20 participants were given questionnaires to collect data for this study. The data is analysed by using Statistical Packages for social science (SPSS). Overall, the study found that the 1 AZAM program was effective. However, there are some problems that arise such as problems of competition, financial problems and unsuitable equipment problems. Program 1 AZAM has a positive impact and increase respondents income and thus can reduce poverty.